Atomic Layer Deposition of TiO2 Nanocoatings on ZnO Nanowires for Improved Photocatalytic Stability. (9th May 2019) - Kao, Emmeline; Park, Hyun Sung; Zang, Xining; Lin, Liwei
Abstract : Photocatalytic water splitting represents an emerging technology well positioned to satisfy the growing need for low-energy, low CO2, economically viable hydrogen gas production. As such, stable, high-surface-area electrodes are increasingly being investigated as electrodes for the photochemical conversion of solar energy into hydrogen fuel. We present a titanium dioxide (TiO2 )/zinc oxide (ZnO) nanowire array using a hybrid hydrothermal/atomic layer deposition (ALD) for use as a solar-powered photoelectrochemical device. The nanowire array consists of single crystalline, wurtzite ZnO nanowires with a 40 nm ALD TiO2 coating. By using a TiO2 nanocoating on the high surface area-ZnO array, three advancements have been accomplished in this work: (1) high aspect ratio nanowires with TiO2 for water splitting (over 8 μ m), (2) improved stability over bare ZnO nanowires during photocatalysis, and (3) excellent onset voltage. As such, this process opens up new class of the micro/nanofabrication process for making efficient photocatalytic gas harvesting systems.